[Using a brain-computer interface by a client with a traumatic brain injury]. - Vincent C; Bisson J; Langlois E; Cantin J (Canadian Journal of Occupational Therapy, 2010)
Background. There is limited knowledge concerning the effectiveness of computer access modes. This article presents a case report of a client with a serious traumatic brain injury who, four years after his accident, tried a brain-computer interface (Cyberlink software). Purpose. To examine the client's computer performance (keyboard and mouse tasks) and the degree of realisation of three occupations (written communication, interpersonal relations and leisure). Methods. A training over 16 weeks (2 X per week) and a follow-up at 3 months were completed. The activation of the computer with Cyberlink was tested with lateral movements of the eyes, relaxation waves, waves of activation of the brain and facial musculature. Findings. After 8 weeks of training with Cyberiink, no improvements were noted in the use of the keyboard and the mouse. The trial of another interface (tactile screen) finally made the optimization of mouse functions possible. Implications. The endurance and memory problems were circumvented with a long, repetitive and flexible training of the computer use.